THE INFLUENCE OF GLOBALIZATION AND UNCERTAINTY OF THE ECONOMIC ENVIRONMENT ON THE MODEL OF ENTERPRISE BEHAVIOR - Klipkova , Oksana; Kozmuk , Natalia; Golub , Anna (Socio-economic relations in the digital society, 2021)
The article examines the concept of «globalization» and the factors of its influence and formation. In particular, the political, legal, market, cost and competition factors that determine the main guidelines of the business environment for countries that are part of the common economic, legal and socio-cultural space. The advantages and disadvantages of globalization processes for business structures and national economies are noted. The essential characteristics of the uncertainty of the enterprise’s behavior during the spread and active development of globalization processes are highlighted. The expediency of using the principles of Abel’s model to reflect the opportunities and losses in creating a common economic space is determined. Recommendations for the formation of the optimal behavioral trajectory of enterprises under conditions of uncertainty based on the choice of strategy taking into account the criteria of Savage, Hurwitz and Walras. In the formation of the article used general scientific methods of induction and deduction — in determining the impact of globalization on enterprises and the national economy, analysis and synthesis — in studying the factors of globalization on the national economy of individual states, scientific abstraction and economic experiment — firms in conditions of uncertainty. It is proved that globalization processes in the world economy will promote the formation of adaptive behavior in enterprises, which is aimed at identifying and classifying the company’s resources, assessing the strengths and weaknesses of the competitive environment, potential and earnings in terms of opportunities for permanent competitive advantage and profit. The authors propose measures that will determine the benchmarks of the optimal behavioral trajectory of the enterprise with these opportunities and limitations, namely: optimization and rationalization of resource use; formation of a stable multilateral information flow and adaptive information processing tools; optimization of the system of planning, accounting and control over the main indicators of the business structure in the direction of improving the system of forecasting and cost planning; formation of the optimal capital structure in order to ensure the growth of international competitiveness; dynamic adjustment of assortment policy, adaptation to quality control systems on the world market.
Keywords: globalization; globalization processes; uncertainty of the economic environment, optimal behavioral trajectory of enterprises